Negotiating Values in Modern India: A Theoretical Exploration. (January 2016) - Vinod, Renu
This article explores the influence of modernity in India, within the larger framework of state-led modernity and its impact on identity and locality. The discourse on modernity has retained the common thread of transience and reflexivity as two constitutive features, both of which are taken up to explain the uncertain and provisional influence of modernity on the Indian society and identity, and the radical engagement of social movements with modernity. The article studies the complex functioning of modernity in India (i) by presenting a theoretical outline on the contested nature of the concept, with an emphasis on the discussion around reflexivity, which forms one of the core attributes for the creation of multiple and alternative modernities, (ii) by reviewing state-led modernity in India and its impact on identity formation as a consequence of the numerous and variable cultural and value systems that confront individuals and (iii) by looking at the local appropriation of contested spaces to enter into a radical, value-based engagement with global modernity.